Hubungan Antara Teknik Anestesi pada Pasien Sectio Caesarea dengan Kejadian Hipotensi Pasca Anestesi di RSUD dr. Soedirman Kebumen - Fitrah Annisa Az Zahra; Dwi Novitasari; Surtiningsih Surtiningsih (Pusat riset dan Inovasi Nasional, 2025)
Both regional and general anesthesia techniques carry the risk of hypotension through different mechanisms. Regional anesthesia often causes hypotension due to sympathetic nerve blockade, which leads to peripheral vasodilation and a decrease in blood pressure. On the other hand, general anesthesia lowers blood pressure through its depressive effects on the cardiovascular system. Hypotension occurs more frequently in patients undergoing regional anesthesia compared to general anesthesia. This study aims to determine the relationship between anesthesia techniques and the incidence of post-anesthesia hypotension in Sectio Caesarea (SC) patients at RSUD dr. Soedirman Kebumen. This study uses a correlation analytic method with the Chi-Square test and a cross-sectional approach. Samples were taken using purposive sampling, consisting of 60 patients, 30 who received general anesthesia and 30 who received regional anesthesia. The research method involved blood pressure observation, which was then analyzed. The results showed that 26 patients (43.3%) in the regional anesthesia group experienced hypotension, while only 1 patient (1.7%) in the general anesthesia group experienced hypotension, with a p-value of 0.000. Based on these results, it can be concluded that there is a significant relationship between anesthesia techniques and the occurrence of hypotension, where regional anesthesia poses a higher risk for post-anesthesia hypotension in SC patients.